Public Support for Sustainable Development: A Mile Wide, but How Deep? - Vasi, Ion Bogdan (Consilience, 2012)
This article argues that public recognition of problems related to sustainable development and public support for domestic and international actions to address these problems is a major challenge for policies that aim to balance the needs of billions of people with the needs of the planet. The article reviews opinion polls on various topics related to global sustainable development, as well as research on the relationship between attitudes, behaviors, and collective actions. It also reflects on future prospects for changing the public support for sustainable development from “a mile wide and an inch deep” to “a mile wide and deep.”